Strengthening family nutrition literacy based on community nursing in stunting prevention in toddlers - Ari Setiawati; Indra Tri Astuti (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2026)
Stunting remains a major public health problem that threatens child growth and long-term human development, particularly in low- and middle-income countries. Family nutrition literacy plays a critical role in shaping feeding practices, health-seeking behavior, and early detection of growth problems among toddlers. This community service program aimed to strengthen family nutrition literacy through a community nursing based approach to support stunting prevention among toddlers. The program was implemented using a community-based method involving five stages: socialization, training, application of technology, mentoring and evaluation, and program sustainability. Activities were conducted with 30 families who had toddlers, supported by community nurses and health cadres. Training focused on balanced nutrition, appropriate complementary feeding, dietary diversity using local food sources, food hygiene, and interpretation of growth monitoring results. Simple digital educational media and mobile communication were used to reinforce learning and follow-up. Mentoring was provided through home visits and counseling sessions to support behavior change. The results showed improvements in family nutrition literacy, indicated by a reduction in low literacy levels and an increase in good literacy levels after the intervention. Positive changes were also observed in feeding practices and compliance with regular toddler growth monitoring. These findings indicate that strengthening family nutrition literacy through community nursing is an effective strategy to enhance family capacity in stunting prevention. Integrating education, mentoring, and appropriate technology within routine community nursing services can contribute to sustainable improvements in child nutrition practices. This approach has the potential to support long-term stunting reduction by empowering families as active agents in child health and nutrition care